Magnetic nanochains for biosensing - Wong, See Min (2016)
This project explores the potential of using mussel-inspired polydopamine (PDA) to construct multifunctional magnetic nanochains that could detect biomarkers of cancer cells and kill the cancer cells. Self-assembly of PDA on the surface of the assembled magnetic nanoparticles offers the opportunity for surface modification by attaching biomolecules such as DNA aptamer, which bind specifically to biomarkers on the cancer cells. Eventually, leading to magnetolysis of the cancer cells under spinning magnetic field. To obtain such magnetic nanochains, miniemulsion of magnetite nanoparticles were first synthesized and reacted in a three-necked round-bottomed flask in an inert system to get magnetic nanoparticles. Magnetic Fe3O4 nanoparticles were subsequently induced to assemble into magnetic nanochains under the influence of magnetic field. Thereafter, magnetic field was turned off to allow the coating of PDA on the surface of the nanochains. Bioconjugation then followed after by adding DNA aptamer to the dispersed nanochains. Aptamer-nanochains were then added to MCF-7 human breast cancer cells for dark field and fluorescence imaging, and cytotoxicity analysis. Results have show 80% cell deaths for MCF-7 cells that were treated for an hour with aptamer-nanochains under spinning magnetic field. Moreover as the concentration of aptamer-nanochains increases, it results in a higher percent of cell deaths. It is evident that aptamer-nanochains are able to kill the cancer cells effectively under a spinning magnetic field as it has a high binding efficiency to the biomarkers on MCF-7 cells.